Does Spinal Cord Stimulation Really Influence Sleep?. Issue 3 (26th September 2018) - De Jaeger, Mats; Goudman, Lisa; De Groote, Sander; Rigoard, Philippe; Monlezun, Olivier; Moens, Maarten
Abstract : Background: To date, clinical pain research has typically used subjective questionnaires to assess effectiveness of treatment. However, in the near future, new technologies may provide us objective outcome measures as an alternative to self‐report. The goal of this study is to compare subjective and objective sleep assessments in a population of failed back surgery syndrome (FBSS) patients, treated with spinal cord stimulation (SCS). Methods: Twenty‐two patients diagnosed with FBSS received SCS. Sleep data was collected at three time point: prior to SCS implantation (B), one month after SCS (T1), and two months after SCS (T2). Sleep data measured by actigraphy provided objective sleep data and were compared to Pittsburgh sleep quality index (PSQI) scores. Agreement between sleep parameters, total sleep time (TST), sleep efficiency (SE), and sleep onset latency (SOL), was examined. Results: Nineteen out of 22 patients completed the study. We identified significant differences between objective and subjective measurements for TST and SE at baseline and after two months of SCS, with patients underestimating both parameters on the PSQI in comparison to objective measurements. For SOL no significant differences were found, although patients subjectively overestimated SOL at B. Conclusion: The results about sleep measurements shown in this population of chronic pain patients, suggest that the subjective ratings scored worse than the objective measurements. Second, short‐term SCS mainly seems to affect subjectively measured sleep parameters, especially SOL. This study shows the discrepancies between objective and subjective assessments in chronic pain research. Objective tools are indispensable for a correct assessment and treatment of sleep parameters. They are also playing a role as a biofeedback tool and are supporting the rehabilitation process.